Detection of β-lactams and Tetracyclines Antimicrobial Residues in Raw Dairy Milk for Human Consumption in Palestine - AL ZUHEIR, Ibrahim Mahmoud (Walailak Journal of Science and Technology (WJST), 2012)
Milk and milk products are among the most important daily consumed foodstuffs. The quality and safety of raw milk for human consumption in developed countries is not adequately monitored. The lack of studies about the antimicrobial residues in milk keeps this vital topic under observation. In this brief study, 34 raw dairy milk samples were tested for detection of antimicrobial residues of β-lactams and tetracyclines above Maximum Residual Limits (MRLs). Rapid screening test, IDEXX Snap test kit was used in this study. Eighteen samples were tested for β-lactams residues, of which 22.2 % (4 of 18) appeared to be above MRLs. Sixteen samples tested for tetracycline of which 18.7 % (3 of 16) were above MRLs. This is the first report that highlights the occurrence of antimicrobial residues marketed raw milk for human consumption in Palestine.